Pengaruh Kepemimpinan dan Tingkat Pendidikan terhadap Kinerja degan Motivasi Kerja sebagai Variabel Intervening pada Perangkat Desa Kecamatan Lubai Ulu Kabupaten Muara Enim - Dita Fickriyani Rahayu; Diah Isnaini Asiati; Junaidi Junaidi (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study examines the effects of leadership and education level on the motivation and performance of village officials in Lubai Ulu District, Muara Enim Regency, with motivation serving as a mediating variable. An associative research design with a quantitative approach was employed. The study involved 139 village officials as the population, from which 112 respondents were selected using cluster random sampling. Primary data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with LISREL. The findings indicate that leadership and education level have significant positive effects on both motivation and performance. Motivation also has a significant positive effect on employee performance. Furthermore, motivation mediates the relationships between leadership, education level, and the performance of village officials. These findings suggest that effective leadership and higher educational attainment enhance employee motivation, which in turn improves organizational performance